Implementation of Round and Grab Fun Game to Improve the Cognitive Abilities of Early Childhood - Khasana, Niswatul; Kumala, Farida Nur; Muntomimah, Siti (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This classroom action research aims to improve the cognitive abilities of 4-5-year-old children at TK Muslimat NU 1 Tumpang through the Round and Grab Fun game. The research subjects consisted of 20 students, including 11 boys and 9 girls. The study was conducted in two cycles using the Kemmis and McTaggart model, which consists of four stages: planning, action, observation, and reflection. The results showed that after Cycle I, the children's cognitive abilities improved by 60%, from an initial observation of only 35%, but this result was still not optimal as the expected success rate was 75%. This affected the outcome in Cycle II, where the children's cognitive abilities improved by 85%. Therefore, it can be concluded that the implementation of the Round and Grab Fun game can improve the cognitive abilities of 4-5-year-old children at TK Muslimat NU 1 Tumpang.